Istihsan Sebagai Metode Istimbath Hukum Imam Hanafi Dan Relevansinya Dalam Pengembangan Ekonomi Syariah - Nur'aini, Arif; Muhammad Ngizzul , Muttaqin (Tribakti: Jurnal Pemikiran Keislaman, 2020)
As a scientific of term that has an important role in the development of Islamic science. Islamic economics is considered important to get attention and development of study. Islamic economics is an entity of thought and practice that is currently stretching among of Moslem's. In every thought of entity, it has its own methodology and framework of thinking. Likewise with a theoretical framework regarding Islamic Economics. One of the Islamic Economic methodology frameworks that are different from conventional of methodologies economic, it is a framework of thinking that starts from ushul fiqh (istimbath legal of method). Ushul fiqh has a very strong role in contributing to the emergence of Islamic economics. Istihsan as one of the istimbath methods of Islamic law (ushul fiqh) initiated from by Imam Hanafi. certainly must be given more portions in order to further develop the Islamic economy. As a literature-based study, this study has significance to the development of Islamic economics through the istihsan method. The findings in this study are expected to add new treasures to the thought of Ushul Fiqh and the development of Islamic economic studies.